Prostate Cancer Immunotherapy: The Path Forward - Madan, Ravi A. (Curr Opin Support Palliat Care, 2017)
PURPOSE OF THIS REVIEW: To provide an overview of current strategies being investigated in the development of immunotherapy in prostate cancer. RECENT FINDINGS: Development of immunotherapy in prostate cancer actually began in 2010 with FDA approval of sipuleucel-T. Given that immune checkpoint inhibitor trials have either been negative at the phase 3 level or underwhelming in smaller studies, it is likely that combination strategies will be required to further maximize the impact immune-based therapies on the clinical course of the disease. Emerging data suggests the presence of multiple checkpoint inhibitors in the prostate cancer tumor microenvironment highlighting the need for combination immunotherapy platforms that would potentially include androgen deprivation, chemotherapy or radiation.